Sistem Informasi Pendaftaran Calon Kepala Desa Pada Panitia Pemilihan Desa Suka Medan Berbasis Web - Sistin Ulandari; Yetman Erwadi; Gunawan Gunawan; Sri Handayani (Universitas Dehasen Bengkulu, 2024)
Data innovation has advanced rapidly through various programming created with today's tools. Special advances sometimes become more modern, we can see it in various everyday matters, for example local correspondence and public administration around the world, simply using email or other web-based media or to register candidates for city heads, interacting with the web and opening site pages creates each of our exercises is simpler and more productive. The aim of this research is to build a website for registering village head candidates through online media. This website was developed in the PHP programming language, MySQL database. This website can facilitate the registration of village head candidates and information about village head candidacy in the village because it only requires an internet connection, and registration can be done anywhere and at any time. The village-level election committee also makes recording data on new village head candidates easier because they can check registrant details directly via the website.